Marktöffnung und Wettbewerb: Das erste Gutachten der Deregulierungskommission - Claus-Friedrich Laaser (Zeitschrift für Verkehrswissenschaft, 1991)
Last year the Commission on Reducing Counterproductive Market Regulations (Deregulation Commission), appointed by the German Federal Government in 1987, put forth its first report dealing with regulations on German transport and insurance markets. Following a consequent market-oriented approach, the commission arrives at the conclusion that the traditional position, i. e. contending that competitive mechanisms would not be feasible for govering supply and demand in transport markets, is highly questionable. Though the deregulation proposals, derived from a thorough economic analysis of the transport markets, may seem radical from such a traditional point of view - even the railway System could nearly entirely be deregulated - the commission's argumentation is convincing and consistent. Its arguments are backed up by evidence from foreign countries' successful experience with deregulating transport markets. Another strong point of the report lies in its combining rigorous economic analysis with practical considerations.
Keywords: 330; Deregulierung; Verkehrspolitik; Deutschland